Management of central giant cell granuloma: discussion of two cases - GILLIAN C. MOONEY, JEREMY McMAHON, SEAN E. WARD, LESLEY E. DAVIDSON, & SARAH NORTH (IAPD and Blackwell, 2007)
The Central Giant Cell Granuloma (CGCG) is an uncommon benign lesion of the jaws.It occurs predominantly in children and young adults, and may cause local destruction of bone and displacement of teeth.